Pengaruh Pola Asuh Orangtua Terhadap Kebiasaan Belajar Siswa Kelas VII B SMP Negeri 2 Tuntang - Dio Rastra Sewakottama; Tritjahjo Danny S; Yustinus Windrawanto (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the significance of the influence of parenting style on the learning habits of class VII B students at SMP Negeri 2 Tuntang. The type of research used is causal comparative to test whether the independent variable (X), namely parenting style, has an influence on the dependent variable (Y), namely study habits. The population in this study were 34 students of class VII B SMP 2 Tuntang and were taken using a sampling technique, namely total sampling or the entire sample according to the study population. The data collection technique in this study used a questionnaire and the research data were analyzed using a simple linear regression technique with the help of the SPSS for windows release 21.0 program. The results showed that there was a significant influence of parenting style on the learning habits of class VII B students at SMP Negeri 2 Tuntang. These results are evidenced by the acquisition of a Tcount value greater than Ttable (3.559 > 2032). Apart from that, an Rsquare value of 0.288 was also obtained, which means that the parenting style variable contributed 28.8% to study habits, while the remaining 71.2% was influenced by other factors/variables not examined in this study.